Event-specific body characteristics of elite Alpine skiers in relation to international rankings - Vermeulen, B.; Clijsen, R.; Fässler, R.; Taeymans, J.; D`Hondt, E.; Aerenhouts, D. (Advances in Anthropology, 2017)
Objective: This explorative study examined potential performance indicators through a correlational analysis between morphological measures and international ranking within each alpine ski event for each gender separately. Methods: A cross-sectional sample of 58 elite alpine skiers were allocated into a technical or speed event group based on their international ski rankings. Several two-way (2 * 2) (M)ANOVA`s were used to examine the effect of gender and event group on age, BMI, sum of 6 skinfolds and somatotype. Forward stepwise discriminant analysis selected the most discriminating somatotype component between gender and/or event. Bivariate Pearson correlations between registered variables and international rankings per alpine ski event were examined for each gender separately. Results: Female speed specialists possessed more relative fat mass (P = 0.022) than female technical specialists. Irrespective of gender, technical specialists were lighter (P < 0.001) and had less relative fat mass than speed specialists (P = 0.008). Pearson values indicated moderate associations between speed rankings and body weight. High female speed rankings were associated with higher relative fat mass. High male speed rankings were associated with lower ectomorphy. Conclusion: Additional body weight appears to be beneficial in SPEED events. Fat mass correlated positively with higher rankings of female SPEED specialists. This observation should be monitored in female alpine skiers so that performance thresholds of relative body fat can be determined.